2023
DOI: 10.3390/biomedicines11030950
|View full text |Cite
|
Sign up to set email alerts
|

Amivantamab-Vmjw: A Novel Treatment for Patients with NSCLC Harboring EGFR Exon 20 Insertion Mutation after Progression on Platinum-Based Chemotherapy

Abstract: Objective: This study is a comprehensive review of the clinical pharmacology, pharmacokinetics, efficacy, safety, and clinical applicability of amivantamab-vmjw for metastatic non-small cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) exon 20 insertion (exon20ins) mutation. Data Synthesis: The literature search to identify clinical trials returned only the CHRYSALIS phase 1 study. In a phase I trial, amivantamab-vmjw was associated with an overall response rate (ORR) of 40% (95% CI, 29–51)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…With the appearance of two EGFR ex20ins inhibitors (mobocertinib and amivantamab), new hope has been given to patients with EGFR ex20ins NSCLC. Clinical study results indicated amivantamab to be effective in 40% of patients with lung cancer who have failed platinum chemotherapy, with a median PFS of 8.3 months and a median overall survival of 22.8 months ( 23 , 24 ). Mobocertinib received accelerated United States Food and Drug Administration (FDA) approval on September 15, 2021, for the treatment of locally advanced or metastatic adult NSCLC for patients with the EGFR ex20ins mutation ( 25 , 26 ).…”
Section: International Multidisciplinary Team (Imdt) Discussionmentioning
confidence: 99%
“…With the appearance of two EGFR ex20ins inhibitors (mobocertinib and amivantamab), new hope has been given to patients with EGFR ex20ins NSCLC. Clinical study results indicated amivantamab to be effective in 40% of patients with lung cancer who have failed platinum chemotherapy, with a median PFS of 8.3 months and a median overall survival of 22.8 months ( 23 , 24 ). Mobocertinib received accelerated United States Food and Drug Administration (FDA) approval on September 15, 2021, for the treatment of locally advanced or metastatic adult NSCLC for patients with the EGFR ex20ins mutation ( 25 , 26 ).…”
Section: International Multidisciplinary Team (Imdt) Discussionmentioning
confidence: 99%
“…9 Amongst those, early monovalent and bivalent mAb approaches relied on antagonism and antibody-dependent cellular cytotoxicity (ADCC) as the main modes of action and failed in clinical development. 10–12 Next-generation biologics were designed as bispecific antibodies, such as amivantamab 13 or MM-131, 14 or focused on target degradation. 15–17 One molecular mechanism for effective target degradation is crosslinking of more than two target molecules via dual binding of suitable combinations of paratopes and their optimal orientation in a biparatopic antibody to favor inter- over intra-molecular binding ( Figure 1a ).…”
Section: Introductionmentioning
confidence: 99%
“…Amivantamab (JNJ-61186372) (7,15,(25)(26)(27) is a bispecific antibody targeting EGFR and MET, exhibiting immune celldirected activity. Due to its promising efficacy and safety profile, on May 21, 2021, the United States Food and Drug Administration (FDA) granted approval for its use in the treatment of EGFR-exon20ins in platinum-based chemotherapy-experienced or treatment-naïve patients with metastatic NSCLC (28,29).…”
Section: Introductionmentioning
confidence: 99%